Financial support for the growth of small - goyal, aanchal (2009)

(untitled)
The paper does a comparative analysis of e of Small and Medium Enterprises (SME) in India and UK. It studies the past and present of this industrial segment and tries to predict the future prospects of the industry. The objective of the research is to analyze the performance of small and medium enterprises engaged in India and the lessons it should learn from its UK counterparts